The Role of the Mosque as a Center for Islamic Religious Education in Developing Youth with Religious Character in Barangka Village, Buton Regency - Merlin, Merlin; Maudin, Maudin; Sulasri, Sulasri (Journal of English Language and Education, 2025)
This study aims to examine and analyze the role of the mosque as a center for Islamic religious education in developing the religious character of youth in Barangka Village, Buton Regency. In rural communities, the mosque functions not only as a place of worship but also as a non-formal educational institution with significant potential in shaping the morals and personality of the younger generation. In the face of globalization and the rapid development of information technology, which influence youth lifestyles and mindsets, character education based on Islamic values becomes increasingly crucial and relevant. This research employs a qualitative descriptive approach, using data collection methods such as observation, in-depth interviews, and documentation of religious activities conducted at the mosque. The informants include religious leaders, youth, mosque youth organization members, and the surrounding community. The findings reveal that the mosque in Barangka Village organizes a variety of structured religious education activities, including regular study sessions, Qur’an reading lessons, religious discussions, and community-based Islamic events aimed at reinforcing religious values among the youth. Youth involvement in these activities significantly contributes to the development of their religious character, as evidenced by increased devotion to worship, polite behavior, social responsibility, and active participation in community life. Despite several challenges, such as limited facilities, a shortage of qualified religious educators, and negative influences from digital media, the mosque remains a vital moral foundation for the youth—supported by religious figures, families, and the broader community. This study concludes that the mosque plays a strategic role in educating and nurturing religiously grounded youth, and with institutional strengthening and cross-sector collaboration, this role can be further optimized to meet the demands of modern character education.